Internalization of Basic Value of SÄlih Akram (BVSA) as Efforts to Establish the Moral of Students of Institute Mathali'ul Falah (IPMAFA) Pati Central Java - M. Lutfi Setiawan; Muawanah Muawanah (Didaktika Religia, 2019)
This article intends to know and understand the development of concepts, objectives, methods, results and evaluation of internalization of BVSA in IPMAFA Pati. Todayâ€™s global world moves by bringing change more quickly and competitively, various fields experience shifts and challenges, including moral and moral crises in higher education institutions. Character education comes as a solution to the problem of morality, which we often encounter in various boarding schools. The Mathaliâ€™ul Falah Pati Boarding School in Central Java is an Islamic tertiary institution that synergizes with Maâ€˜had al-JÄmiâ€˜ah. It has the concept of the Basic Values of SÄlihÂ Akram (BVSA) as an effort to prepare generations who have good professionalism and morality. This article was prepared using a qualitative-descriptive approach. Data collection methods used is field observations, interviews, and documentation studies. The results of this study indicate that the BVSA concept is values derived from Islamic boarding schools, which are being developed by IPMAFA Pati and become a scientific paradigm. The internalization of BVSA in IPMAFA Pati and Maâ€˜had al-JÄmiâ€˜ah is Integration, Interconnection, and Insertion by taking into account the ten principles of BVSA. The results of BVSA internalization in IPMAFA Pati are that students are the regulations made by IPMAFA Pati, which influence them to be aware and understand how to become a generation that has good morals. Evaluation of BVSA internalization of IPMAFA students is based on an assessment of the cognitive and affective domains that appear in the Study Plan Card and Study Result Card.